Avaliação da capacidade de adsorção da torta de Moringa Oleifera para BTEX em amostras aquosas - Almeida, Ione Lucenir Silva (2010)
In this study the adsorption capacity of coumponds benzene, toluene, ethylbenzene, p-xylene e o-xylene (BTEX) on Moringa oleifera seeds cake from aqueous solution was evaluate. The cake were obtained after oil extraction from the seeds with n-hexane. The BTEX compounds were selected because of the environmental impact caused by their presence in the water streams and their high toxicity. The Moringa oleifera seeds cake were characterized by thermogravimetric analysis, infrared spectroscopy, X ray diffraction and Point of Zero Charge. The variables of the adsorption process such as contact time and solution pH were studied to optimize the maximum adsorption conditions. The results obtained, contact time (20 min) and solution pH (7) were used for building the adsorption isotherms. The Langmuir and Freundlich linear isotherm models were applied to the experimental data to describe the adsorption process. The adsorption process was described satisfactorily by the Freundlich equation. This study shows that the Moringa oleifera seeds cake exhibits the good adsorption capacity and can be used for adsorbs BTEX in aqueous solution.